Effect of Glass Fiber Addition on the Compressive and Tensile Strength of Concrete - Yildiz, Servet; Bolukbas, Yakup; Kelestemur, Oguzhan (Gazi Univ, 2010)
Concrete is a material which has very wide application range in the structural application. However, because of its brittleness, sometimes it should be supported by different material. Glass fiber is one of the added materials for increasing the ductilite of concrete. Fiber glass addition increases the resistance of concrete by preventing to spread of cracks occurred in concrete. In this study, 300 and 350 dosages concrete samples which have constant water/cement ratio and strength class C30 have been prepared and pulse velocity, compressive and tensile strength of these samples have been investigated for the determining effect of the glass fiber addition on the strength of concrete. As a result of the study, especially 5 and 10 kg/m(3) glass fiber addition have been increased the compressive strength of the concrete. Additionally, while the tensile strength of the concretes have increased depending on the rise of the glass fiber ratio, ultrasonic pulse velocity values have also reduced.
Keywords: Concrete; Fiber Glass; Pulse Velocity; Compressive Strength; Tensile Strength